2019
DOI: 10.3390/vision3040060
|View full text |Cite
|
Sign up to set email alerts
|

The Horizontal Raphe of the Human Retina and its Watershed Zones

Abstract: The horizontal raphe (HR) as a demarcation line dividing the retina and choroid into separate vascular hemispheres is well established, but its development has never been discussed in the context of new findings of the last decades. Although factors for axon guidance are established (e.g., slit-robo pathway, ephrin-protein-receptor pathway) they do not explain HR formation. Early morphological organization, too, fails to establish a HR. The development of the HR is most likely induced by the long posterior cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…The PAMM lesion for our patient was also noted to occur in the area between the superior and inferior retinal vascular arcade, along the horizonal raphe (HR), which has also been described as a watershed zone. 13 Given the etiology of PAMM, our patient may represent a unique demonstration of a dual watershed effect due to both the vertical intraretinal location of the affected DCP, and the horizontal positioning within the HR. 6 , 13 …”
Section: Discussionmentioning
confidence: 83%
“…The PAMM lesion for our patient was also noted to occur in the area between the superior and inferior retinal vascular arcade, along the horizonal raphe (HR), which has also been described as a watershed zone. 13 Given the etiology of PAMM, our patient may represent a unique demonstration of a dual watershed effect due to both the vertical intraretinal location of the affected DCP, and the horizontal positioning within the HR. 6 , 13 …”
Section: Discussionmentioning
confidence: 83%
“…The retina presents a temporal horizontal raphe that divides the retina into 2 hemispheres: superior and inferior [ 4 ]. These hemispheres contain 2 different vascular systems that communicate only at the level of the 3 capillary plexuses, but in the parafovea only at the level of the deep capillary plexus [ 2 , 3 ]. However, at the temporal raphe, there is a distinct separation between the nerve fiber layer of the superior and inferior temporal retina, and this has been attributed to the earlier development of the central retina and to the existence of the 2 watershed zones [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, at the temporal raphe, there is a distinct separation between the nerve fiber layer of the superior and inferior temporal retina, and this has been attributed to the earlier development of the central retina and to the existence of the 2 watershed zones [4]. The separate circulation of the superior and inferior hemispheres of the temporal retina might be a consequence of development and, in particular, of the organization of the long posterior ciliary arteries, and it has been suggested that it may also play a protective role in the case of vascular occlusive diseases [3]. Retinal vessel development initiates in the optic nerve and proceeds centripetally, respecting the temporal raphe and reaching the retinal periphery before birth [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations